2020
DOI: 10.3390/molecules25133010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Mitochondrial BKCa Channel by the Citrus Flavonoid Naringenin as a Potential Means of Preventing Cell Damage

Abstract: Naringenin, a flavanone obtained from citrus fruits and present in many traditional Chinese herbal medicines, has been shown to have various beneficial effects on cells both in vitro and in vivo. Although the antioxidant activity of naringenin has long been believed to be crucial for its effects on cells, mitochondrial pathways (including mitochondrial ion channels) are emerging as potential targets for the specific pharmacological action of naringenin in cardioprotective strategies. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…We have also demonstrated using patch clamp that naringenin directly activates the mitoBK Ca channel from endothelial mitochondria. Furthermore, naringenin prevents cell damage in this model [204]. Thus, mitochondrial ion channels are becoming promising new targets for flavonoids in cells.…”
Section: Mitochondrial Ion Channel Openersmentioning
confidence: 76%
See 1 more Smart Citation
“…We have also demonstrated using patch clamp that naringenin directly activates the mitoBK Ca channel from endothelial mitochondria. Furthermore, naringenin prevents cell damage in this model [204]. Thus, mitochondrial ion channels are becoming promising new targets for flavonoids in cells.…”
Section: Mitochondrial Ion Channel Openersmentioning
confidence: 76%
“…Moreover, naringenin-induced activation of mitochondrial K + channels leads to mild mitochondrial uncoupling and results, as expected, in an increase in the mitochondrial respiration rate in these cells. In addition, our latest study indicates that in mitochondria isolated from human endothelial cells, naringenin stimulates inhibitor-sensitive mitoBK Ca channel-mediated K + flux, decreasing the mΔΨ and thus accelerating the mitochondrial oxygen consumption rate [ 204 ]. We have also demonstrated using patch clamp that naringenin directly activates the mitoBK Ca channel from endothelial mitochondria.…”
Section: Flavonoids In Mitochondrial Pathwaysmentioning
confidence: 99%
“…All those features illustrated the model of PCOS were established. Interestingly, a avanone, naringenin extracted from citrus fruits and exist in many traditional Chinese herbal medicines, has been displayed to have multiple effective effects on cells both in vivo and in vitro [30]. The result of naringenin treatment was the estradiol level and ISI increased, the T, LH, FSH, FBG, FINS and HOMA-IR levels decreased when compared to the levels in PCOS group.…”
Section: Discussionmentioning
confidence: 99%
“…The conducted research has also shown that naringenin increasing the concentrations of enzymes removing reactive oxygen species and reducing oxidative stress is one of the characteristics of polycystic ovary syndrome. The cytoprotective and anti-inflammatory effects of naringenin were also described in [ 134 ], where the authors described the naringenin-mediated protection of cells against damage induced by TNF- in combination with cycloheximide in an in vitro experiment. The described properties of naringenin justify considering it as an element of PCOS therapy [ 133 ].…”
Section: Potential Drug Targets and Active Substances In Novel Thementioning
confidence: 96%